(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Some students feel difficult to master speaking skill in English, because they do not get support from their atmosphere. The environment is not an English area. So they need to practice their speaking by using media .This study aimed to determine how students felt about using the Cake application to improve their speaking skills. This study involved eight students from class XI MIPA 4 at MAN 1 Medan. The researchers employed the qualitative descriptive approach in this research. Interviews and questionnaires were used to gather data. The majority of students reported that the Cake application was highly beneficial in helping them improve their speaking skills, according to the study’s findings, because those unfamiliar with the Cake program will find it simple to utilize. Then, when students use this cake application to hone their speaking abilities, they become intrigued. Most of them do not feel bored when using this application because they can learn the idioms by watching the short English film in this application. Of course, it is fun for the students. They said that by using this application, they could practice their English speaking wherever and whenever only by using the smartphone and opening the cake application. Furthermore, they will invite their friends to use the cake application because this application is suitable for students who want to practice speaking without feeling shy about meeting many people. Finally, they said they would use the cake application daily to improve their English speaking skills.